Factors Associated With In Vitro Interferon-gamma Production in Tuberculosis - Yu, Chung-Chieh; Liu, Yu-Chih; Chu, Chien-Ming; Chuang, Duen-Yau; Wu, Wen-Chen; Wu, Huang-Pin (Journal of the Formosan Medical Association, 2011)
Macrophage activation assisted by interferon-gamma (IFN-γ) is a primary mechanism by which Mycobacterium tuberculosis is killed, but IFN-γ (production is inhibited in tuberculosis (TB) patients. The production of IFN-γ is influenced by many factors, such as interleukin (IL)-10, IL-12, IL-18, and clinical diseases; but the relative importance of each factor is unclear. We evaluated the effects of these factors in 46 healthy individuals, 81 patients with TB, and 88 patients with non-TB pneumonia. The responses of IFN-γ, IL-10, IL-12 and IL-18 were determined from phytohemagglutinin-stimulated peripheral blood mononuclear cells (PBMCs). General linear model analysis showed that disease status and IL-12 response were the independent factors associated with the IFN-γ response. The production of IFN-γ was not affected by IL-10 and IL-18. There was a significant relationship between the IFN-γ response and the IL-12 response among patients with non-TB pneumonia, patients with TB, and healthy participants (Pearson's correlation coefficients of 0.466, 0.483, and 0.464, respectively). Production of IFN-γ in PBMCs was associated with active pulmonary TB and IL-12 response.